Incidence of surgical site infections in sub-Saharan Africa: systematic review and meta-analysis - (:unkn) unknown (My University, 2016)
INTRODUCTION: Surgical Site Infections (SSI) cause morbi-mortality and additional healthcare expenditures. Developing countries are the most affected. The objective was to estimate the pooled incidence of SSI in Sub-Saharan Africa and describe its major risk factors. METHODS: Systematic review and meta-analysis were conducted using the databases of the World Health Organization Regional Office for Africa, PubMed and standard search to select electronic articles published between 2006 and 2015. Only articles investigating SSI impact and risk factors in Sub-Saharan African countries were retained. RESULTS: Out of 95 articles found, 11 met the inclusion criteria. Only 9 countries out of 45 have contributed, with a huge amount of information coming from Nigeria (5 articles out of 11). The impact of SSI ranged from 6.8% to 26% with predominance in general surgery. The pooled incidence of SSI was 14.8% (95% CI: 15,5-16,2%) with significant heterogeneity according to the specialty and the method of monitoring. Most cited risk factors were long procedure length and categories 3 and 4 of Altemeier contamination class. Other factors included hospital environment, inadequate care practices and underlying pathologies. CONCLUSION: SSI incidence is high in Sub-Saharan Africa. Studies in this area could improve knowledge, prevention and control of these multiple risk factors.
Keywords: African Research